(untitled) (International Journal of Nursing Education, 2021)
Background: Bullous Pemphigus (BP) is a group of life-threatening autoimmune bullous diseases characterized by flaccid blisters and erosions of the mucous membranes and skin. Autonomy and Independence theory adopted by Virginia Henderson to care for people affected by bullous pemphigus diseases help nurses during their job to assist those patients. Main body: The aim of this study was to assess the effect of application of Henderson theory on nursing care for bullous pemphigus patients. Patients and methods: quasi experimental pretest- posttest design carried out on 31 nurses working in Khartoum dermatology and venereology hospital. Results: Virtually 63% of nurses didn’t have perfect knowledge regarding nursing care for pemphigus diseased patients based on the concept of Henderson theory following application program, nurses knowledge rose to 80.73%. The percentage revealed statistically significant improvement on nurses knowledge (P-value < 0.001). The practical activities of the nurses showed significant improvement on physiological concepts assessments from 49.06% to 77.7%. Emotional and mental concepts from 14.00% to 68.8, social and spiritual concepts from 22.00% to 71.1%, (P-value < 0.001). Conclusion: Utilization of Henderson theory into clinical practice induced significant change on knowledge and practice among nurses in respect to nursing care for pemphigus diseased patients. Recommendations: Utilizations of theory and theory-based evidence to structure their practice, it improves the quality of care and safe time. Organization of regular educational program which gives a chance to reassess proper application of nursing theories concepts in clinical practice.